Beneméritos empresários: história social de uma elite de origem imigrante do sul do Brasil (Santa Cruz do Sul, 1905-1966) - Noronha, Andrius Estevam (2012)
The city of Santa Cruz do Sul, in the central region of Rio Grande do Sul, was structured on an economic base that allowed the emergence of business people who acted as an economic elite until 1966. The corpus that delimits the study involves the owners and shareholders of the 76 businesses selected in a news report celebrating the 100th anniversary of the city. The story was published in April 1947, and includes 189 individuals who controlled entrepreneurial activities during the three phases of the development of Santa Cruz: Settlement (1849-1878); Village (1879-1905); City (1906-1947). First, the thesis presents the formation of the businesspeople, who were of German extraction, discussing economic, political and religious aspects of Santa Cruz do Sul. In a second step we characterize the local economic elite through a prosopographic study of the 189 entrepreneurs who began mercantile activities in the context of sttlement, village and city, to visualize the dynamics of the group over time, using the religious factor as the guiding element in crossmatching the data. Thirdly we discuss the construction of the social network through case studies concerning patrimonial composition, marital ties and transmission of social, entrepreneurial and political capital in different contexts of the action of this elite, be it in the settlement, village or city. As a fourth step we look at the social network structured by the local businesspeople based on two large companies: the Caixa Cooperativa de Crédito Santa-Cruzense (Santa Cruz Cooperative Credit Savings Bank), later called Banco Agrícola Mercantil S/A., (Mercantile Agricultural Bank), the largest private bank in Rio Grande do Sul, and the Companhia de Fumos Santa Cruz S/A, the largest cigarette manufacturer in the south of Brazil. We analyze the composition and construction of the social network of these two companies to visualize the close relationship between financial capital and tobacco-based capital in the city. The biographic sources used were obituaries, locally published biographies and inventories in many different archives. The entrepreneurial sources comprised 25, 50 and 100-year old monographies which were elaborated by local businesses, financial balance sheets and articles written for advertisement purposes. The research was done at the Center for Historical Documentation at the University of Santa Cruz do Sul, the Public Archive of Rio Grande do Sul, the Historical Archive of Rio Grande do Sul, the Archive of the City Council of Santa Cruz do Sul and the archive of the main city newspaper, housed in the Grupo de Comunicação Gazeta do Sul.